Simple, Reliable, and Safe Technique for Endotracheal Tube Cuff Inflation: A Comparative Evaluation of the Three Common Methods - Al-Metwalli, Roshdi R.; Al-Ghamdi, Abdulmohsen A.; Mowafi, Hany A.; Sadek, Sayed; Abdulshafi, Mohammed; Mousa, Wesam F. (Medical Research and Its Applications Vol. 3, 2024)
The aim of this study is to compare the three common (Sealing pressure, precise standard pressure or finger estimation) regarding the effective tracheal seal and the incidence of post-intubation airway complications. Tracheal arterial capillary pressure decreases when the cuff exerts pressure greater than 30 cm H2O, causing tracheal ischemia proportional to the pressure exerted by the cuff and to the duration of exposure. There is a strong relationship between endotracheal cuff pressure and airway complication; therefore, the methods of endotracheal tube cuff inflation are of great importance to maintaining safe and effective cuff pressure. Seventy-five adult patients scheduled for N2O-free general anesthesia were enrolled in this study. After induction of anesthesia, endotracheal tubes size 7.5 mm for females and 8.0 mm for males were used. Patients were randomly assigned into one of three groups. Control group (n=25), the cuff was inflated to a pressure of 25 cm H2O; sealing group (n=25), the cuff was inflated to prevent air leaks at an airway pressure of 20 cm H2O and finger group (n=25), the cuff was inflated using finger estimation. Tracheal leaks, the incidence of sore throat, hoarseness and dysphagia were tested. Although cuff pressure was significantly low in the sealing group compared to the control group (P<0.001), the incidence of sore throat was similar in both groups. On the other hand, cuff pressure as well as the incidence of sore throat was significantly higher in the finger group compared to both the control and the sealing group (P<0.001 and P=0.008). The incidence of dysphagia and hoarseness were similar in the three groups. None of the patients in the three groups developed air leaks around the endotracheal tube cuff. The incidence of sore throat was significantly higher in the finger group compared to both the sealing and control groups, whereas the incidence of both hoarseness and dysphagia was similar in the three groups. Conclusions: When it comes to efficient sealing and a low rate of sore throat, sealing cuff pressure in N2O-free anesthesia is a simple, undemanding, and safe substitute for the conventional method.